Microengineered CH3NH3PbI3 Nanowire/Graphene Phototransistor for Low‐Intensity Light Detection at Room Temperature. Issue 37 (14th July 2015) - Spina, Massimo; Lehmann, Mario; Náfrádi, Bálint; Bernard, Laurent; Bonvin, Eric; Gaál, Richard; Magrez, Arnaud; Forró, László; Horváth, Endre
<x xml:space="preserve">Abstract</x> The first hybrid phototransistors are reported where the performance of a network of photoactive CH3NH3PbI3 nanowires is enhanced by CVD‐grown monolayer graphene. These devices show responsivities as high as ≈2.6 × 106 A W−1 in the visible range, showing potential as room‐temperature single‐electron detectors.